The effectiveness of the community reinforcement approach (CRA) in the context of quality of life and happiness among people using drugs - Khalid, Muhammad Talha; Khalily, Muhammad Tahir; Saleem, Tamkeen; Saeed, Fahimeh; Shoib, Sheikh (Frontiers in Public Health, 2024)
Introduction: Community Reinforcement Approach is an evidence-based treatment modality for alcohol and drug addiction treatment with proven efficacy and cost-effectiveness. The present study investigated the Effectiveness of Community Reinforcement Approach (CRA) in the context of Quality of Life among the Drug Addicts. Material & methods: 60 inpatient substance abusers after detoxification in Fountain House, Lahore, Pakistan participated in this study. Fountain House, Lahore was selected as majorly Minnesota model is used there. Therefore, a new treatment approach was introduced to see its effectiveness for the individuals with substance abuse. A randomized, 12-week trial was conducted as a substance use disorders (SUDs) treatment program. Persons with SUD (i.e., identified patient) enrolled in a residential treatment program were randomized to integrated model of Community Reinforcement Approach (CRA) & traditional Minnesota model treatment (n=30) and traditional Minnesota model treatment only (TMM) (n=30). All of the participants in experimental group attended the group therapy sessions and other activities in the facility in addition to the treatment conditions. The participants went through the individual therapeutic session according to the CRA guidelines in experimental group. In this study each individual in CRA treatment group received 12 one-to-one sessions ranging from 45 minutes to 1 hour. The WHOQOL-BREF scale and Happiness Scale (Meyers & Smith, 2000) were used for data collection. Result: The results showed a significant increase in the quality of life in participants of the treatment group with CRA than the Control Group with TMM. Findings also indicated that the individuals in the treatment group with CRA had improved levels of happiness in comparison to individuals with TMM. Discussion: CRA is an effective and adaptable treatment approach which exhibits quality combinations with other treatment approaches. The proven efficacy, compatibility and cost-effectiveness distinct it from other treatment methods. Implications: CRA should be adapted, assessed and evaluated further in this regard, especially in Pakistan, where there is a pressing need to adopt treatment strategy for addiction problem having proven efficacy.